Eutectic mixture-directed kinetics of Diels-Alder reaction - Nagare, Amit S.; Kumar, Anil (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2011)
In the search for environmentally benign solvent media, a new class of solvents composed of mixtures of carbohydrates with urea or methylated urea has been noted to be effective in enhancing the reaction rates of a bimolecular organic reaction like the Diels-Alder reaction of cyclopentadiene with methyl acrylate. The viscosity of these media appears to be an important parameter in controlling the second order kinetics.
Keywords: carbohydrates; Cycloaddition; Diels-Alder reaction; Dimethylurea; kinetics; Reaction rates; solvent effects; Urea; viscosity

High viscosity of ionic liquids causes rate retardation of Diels-Alder reactions - Kumar, Anil; Pawar, Sanjay S. (Science China-Chemistry, 2012)
Second order rate constants, k (2) have been determined for three bi-molecular Diels-Alder reactions to demonstrate that the high viscosity of ionic liquids can be a detrimental property in carrying out Diels-Alder reactions, if ionic liquids are employed as solvent media. It is possible to enhance the reaction rates of the reaction if a co-solvent is mixed in pure ionic liquid used as a solvent.
Keywords: Diels-Alder reactions; ionic liquids; kinetics; viscosity

Spectacular rate enhancement of the diels-alder reaction at the ionic liquid/n-hexane interface - Beniwal, Vijay; Manna, Arpan; Kumar, Anil (Chemphyschem, 2016)
The use of the ionic liquid/n-hexane interface as a new class of reaction medium for the Diels-Alder reaction gives large rate enhancements of the order of 10(6) to 10(8) times and high stereoselectivity, as compared to homogeneous media. The rate enhancement is attributed to the H-bonding abilities and polarities of the ionic liquids, whereas the hydrophobicity of ionic liquids was considered to be the factor in controlling stereoselectivity.
Keywords: Diels-Alder reaction; Interfaces; ionic liquids; kinetics; stereoselectivity